Dampak Pembangunan Pabrik Smelter terhadap Peluang Kerja dan Tingkat Pendapatan Masyarakat Tani di Desa Morosi Kecamatan Morosi Kabupaten Konawe - Akbar, Kaisar Jainul; Saediman, Saediman; Rosmawaty, Rosmawaty (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study aims to (1) knowing how development impacts smelters to employment opportunities society (2) find out how income levels the society before and after the construction of smelters (3) find out if there are differences in income before and after the construction of smelters. This research was conducted in the Morosi Village of Morosi Subdistrict Konawe District. The variables of this research that employment opportunities and income level. Population is the purpose of this research is society that benefit directly and indirectly from the existence of the construction of smelters. Society has a direct benefit is a vegetable farmer then switched jobs to become the employees of PT. Virtue Dragon Nickel Industry (VDNI) numbered 20 people and the people that benefit are indirectly is they build businesses around smelters as many as 10 people. Sampling technique is used in this study is saturated sample system/census of all members made in the sample, so that all elements of the population investigated one by one.The results showed that, (1) the impact of the construction of smelters to excellent employment opportunities in the Morosi Village Morosi Subdistrict Konawe District, (2) large farmer income before is Rp 822,946/month, while the income farming Society after the construction of smelters Rp 4,330,000/month, (3) there are differences in income before and after the construction of smelters in the Morosi Village Morosi Subdistrict Konawe District